Notes on the genus Leucolopha (Insecta, Lepidoptera, Notodontidae) with description of a new species from China - Chen, Liusheng; Wang, Min (Zootaxa, 2006)
The genus Leucolopha Hampson, 1896 is reviewed. Leucolopha sinica Chen & Wang, sp. nov., from China is described and illustrated; a distribution map and a key to males of Leucolopha species are provided. The type specimens of the new species are deposited in the Insect Collections of Department of Entomology, South China Agricultural University, Guangzhou, P. R. China.